Insula deep rTMS and varenicline for smoking cessation: A randomized control trial study protocol - Ibrahim, Christine; Malik, Saima; Barr, Mera S.; Blumberger, Daniel M.; Daskalakis, Zafiris J.; Le Foll, Bernard (Frontiers in Pharmacology, 2022)
Background: Current approved therapies for smoking cessation have modest long-term effects for abstinence. The insular cortex has been identified by preclinical and clinical studies as a critical target for addiction treatment. Insula functions can be modulated non-invasively using brain stimulation. It is unknown if deep repeated transcranial magnetic stimulation (rTMS) of the insula can improve smoking cessation of smokers trying to quit using varenicline. Methods: This will be a randomized, double-blind, sham-controlled clinical trial with 50 nicotine dependent smokers looking to quit. They will be randomly assigned to receive either active (10 Hz) or sham insula deep rTMS. Deep rTMS will be administered for four weeks (5 days/week). All participants will receive open label varenicline for 12 weeks. The primary outcome measure will be the 7-day point prevalence abstinence at the end of 12 weeks. The secondary outcomes will be Fagerström Test of Nicotine Dependence, Minnesota Nicotine Withdrawal Scale, Tiffany Questionnaire of Smoking Urges, expired carbon monoxide measurements, cigarettes smoked per day, point prevalence abstinence at end of 4 weeks, prolonged and continuous abstinence at 6 months. The measures will be collected throughout the 3-month treatment period as well as at the 6-month follow up. Discussion: This trial will test for the first time the impact of deep insula rTMS on smoking cessation in smokers treated with varenicline. This trial will use an H-coil specific to the insula, while previous studies have targeted both the insula and prefrontal cortex. This trial will inform on the utility to combine insula deep rTMS with varenicline to improve smoking abstinence rates. Clinical trial registration: Trial registered at https://clinicaltrials.gov/ct2/show/NCT04083144 (Identifier: NCT04083144).